Green Human Resource Management: Its Implementation in a Herbal Medicine Industry Company in Central Java - Wijaya, Enida Eka; Sugiarto, Agus (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study explores employee green behavior through Green Human Resource Management (GHRM) practices. Using qualitative methods - Case studies and evaluation approaches, this study provides an objective picture of the implementation of GHRM in companies and its impact on environmental sustainability. The results show that GHRM has the potential to support environmental sustainability. Despite facing some obstacles, GHRM has proven to be effective in increasing employee engagement in corporate green initiatives, as well as helping companies improve their reputation and operational efficiency. In this study, it can be concluded that top management commitment, supportive organizational culture, and collaboration across all levels of the organization are the keys to successful GHRM implementation, which contributes to environmental conservation and the achievement of corporate sustainability goals.